Research activity of cadets of educational institutions of the Ministry of internal Affairs of Russia - Nikishkin A. V. (Pedagogy and psychology: development prospects, 2017)
The article describes the goals and objectives of the process of training of cadets of educational institutions of the MIA of Russia is aimed at training highly qualified specialists for the internal Affairs bodies of the Russian Federation.
Keywords: курсанты; сотрудники органов внутренних дел; the students; высшие учебные заведения системы МВД России; высококлассные сотрудники полиции; Employees of bodies of internal Affairs; higher educational institutions of the MIA of Russia; high level police officers